Alec's primer - Walter, Mildred Pitts; Johnson, Larry, 1949- (Middlebury, Vt. : Vermont Folklife Center ; Lebanon, N.H. : Distributed by University Press of New England, 2004)
A young slave's journey to freedom begins when a plantation owner's granddaughter teaches him how to read. Based on the childhood of Alec Turner (1845-1923) who escaped from slavery by joining the Union Army during the Civil War and later became a landowner in Vermont.
Keywords: Slavery -- Fiction; African Americans -- Fiction; Reading -- Fiction